2005
DOI: 10.1007/s00418-005-0784-3
|View full text |Cite
|
Sign up to set email alerts
|

Integrin expression in developing human salivary glands

Abstract: The development and complete differentiation of salivary glands is a complex process that involves a large number of co-ordinated events. Little is known about the molecular basis for salivary gland development. However, we have reported previously that integrins appear to play a role. Integrins are heterodimeric transmembrane receptors consisting of one alpha and one beta subunit that play a pivotal role in the interaction of cells with the extracellular matrix. Such interactions regulate the organisation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 27 publications
0
12
0
1
Order By: Relevance
“…The expression of AQP1, 3 and 5 has also been described during mouse salivary gland development, suggesting that aquaporins may also have an important role for the gland formation (Akamatsu et al 2003 ; Larsen et al 2009 , 2011 ; Aure et al 2011 ). This mechanism is driven by branching morphogenesis, which comprises complex and dynamic tissue interactions involving neuronal and endothelial cell interaction, cell proliferation, polarisation, differentiation epithelial-mesenchymal communication and cell death, resulting in a complex network of acinar bulbs and ducts (Cutler 1990 ; Patel et al 2006 ; Lourenço and Kapas 2005 ; Lourenço et al 2007 ; Teshima et al 2016 ). No studies on human development have been reported yet, and this work aims to evaluate the expression pattern of AQP 1, 3 and 5 during human salivary gland morphogenesis, describing them according to each developmental stage and discussing the possible role for those proteins in this process compared to animal models.…”
Section: Introductionmentioning
confidence: 99%
“…The expression of AQP1, 3 and 5 has also been described during mouse salivary gland development, suggesting that aquaporins may also have an important role for the gland formation (Akamatsu et al 2003 ; Larsen et al 2009 , 2011 ; Aure et al 2011 ). This mechanism is driven by branching morphogenesis, which comprises complex and dynamic tissue interactions involving neuronal and endothelial cell interaction, cell proliferation, polarisation, differentiation epithelial-mesenchymal communication and cell death, resulting in a complex network of acinar bulbs and ducts (Cutler 1990 ; Patel et al 2006 ; Lourenço and Kapas 2005 ; Lourenço et al 2007 ; Teshima et al 2016 ). No studies on human development have been reported yet, and this work aims to evaluate the expression pattern of AQP 1, 3 and 5 during human salivary gland morphogenesis, describing them according to each developmental stage and discussing the possible role for those proteins in this process compared to animal models.…”
Section: Introductionmentioning
confidence: 99%
“…This finding helps validate the use of the HA-hydrogel platform for study of cell and matrix dynamics as they occur in salivary gland development. Interactions between cells and basement membrane depend on adhesion molecules and surface receptors, primarily integrins (Loducca et al, 2003; Lourenço and Kapas, 2005; Laine et al, 2008), and thus these molecules typically are expressed concordantly with the basement membrane components during embryogenesis (Li et al, 2003). Unlike in the salivary gland, where formation of the gland involves growth and branching morphogenesis originating from a rudimentary salivary bud, in HA hydrogels, microstructures originate from growth from a single hS/PC or merging of adjacent hS/PC microclusters (Pradhan-Bhatt et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Although this process has been described for all salivary glands, the ability to culture the mouse embryonic submandibular gland (SG) ex vivo has resulted in the vast majority of our knowledge being derived from this organ and as such, this review will focus on its development. SG formation is initiated by the thickening of the oral epithelium that invaginates into a condensed mesenchyme containing an endothelial plexus (6–8 weeks in humans and embryonic day (E) 11.5 in mice) . This single epithelial bud then undergoes rounds of branching morphogenesis, defined by multiple cycles of cleft formation, expansion of end buds (pre‐acini), and duct tubulogenesis which involves the elongation of ducts via KRT19+ duct cell proliferation, condensation of KRT19+ duct progenitor cells at the midline, fusion of microlumen to form contiguous lumen and finally lumen expansion (Figure (a)) .…”
Section: Function and Morphogenesis—an Overviewmentioning
confidence: 99%
“…SG formation is initiated by the thickening of the oral epithelium that invaginates into a condensed mesenchyme containing an endothelial plexus (6-8 weeks in humans and embryonic day (E) 11.5 in mice). [17][18][19] This single epithelial bud then undergoes rounds of branching morphogenesis, defined by multiple cycles of cleft formation, expansion of end buds (pre-acini), and duct tubulogenesis 19,20 which involves the elongation of ducts via KRT19+ duct cell proliferation, condensation of KRT19+ duct progenitor cells at the midline, fusion of microlumen to form contiguous lumen and finally lumen expansion (Figure 1(a)). 21 Innervation of the epithelium occurs at the onset of development: at E12 in mice neural crest-derived neurons coalesce at the primary duct to form a parasympathetic ganglia.…”
mentioning
confidence: 99%